Penerapan Metode Peer Tutoring pada Materi Tata Cara Pengurusan Jenazah dan Hikmahnya untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik Kelas X MAN Kuala Makmur Kabupaten Simeulue - Sudirman (Cyber Media Indonesia, 2021)
The peer tutorial method is one of the learning strategies to help meet the student's Needs in the learning process. The purpose of this study was to improve the activity and learning outcomes of Fiqh by applying the peer tutoring method to the material of the procedure for managing the corpse and its lessons to X grade students of MAN Kuala Makmur, Simeulue Regency. This research is a Classroom Action Research (CAR) with the implementation of the procedure through stages: planning, action, observation, and reflection. The research subjects were 25 students. Data collection techniques through observation, student learning tests, and documentation. Data were analyzed using descriptive qualitative method. The results of the study showed that: (1) the activities of the students in the first cycle, the average activity of students was 3, 2 which was classified as sufficient and in the second cycle to 4.3 which was classified as good. (2) Percentage of completeness of student learning outcomes classically in the initial conditions is only 36%. Then it increased 36% in the first cycle to 72%, and increased by 20 in the second cycle, so that 92% finished in a classical manner. Conclusion: The application of the peer method of tutoring in the material for the procedure for managing the corpse and its lessons can increase the activity and learning outcomes of students, class X MAN Kuala Makmur, Simeulue Regency.